Dogmatik som samtidsteologi - Gregersen, Niels Henrik (Dansk Teologisk Tidsskrift, 2023)
This essay develops a program for defining doctrinal studies as the descriptive and normative study of contemporary Christian thought. “Dogmatics” is contemporary theology in the two-fold sense of studying current varieties of Christian doctrine, worldview formation and ethos, and of constructing coherent and self-reflexive proposals for Christian teachings in contemporary contexts. History of doctrine remains an important sub-discipline which serves the purpose of clarifying basic grammars and continuing patterns of Christian thought. Likewise, the study of major theologians exemplifies how well-winnowed theological proposals of the past may continue to inspire and inform contemporary theology. The focal interest, however, lies in analyzing and re-articulating contemporary expressions of Christian faith, while evaluating the potentials of Christian semantics for future Christian communication practices. The regulative rules of Christian grammars, the fluid forms of Christian semantics, and the communicative potentials of Christian pragmatics thus make up the core subject-matter of contemporary theology. It is furthermore argued that contemporary theology is to be pursued in the interest of the society at large. Yet the field has a special function for the Church. For while contemporary theologians propose, communities of faith dispose when it comes to the fate and fortunes of the theological proposals.